Sexual Function and Associated Factors in Postmenopausal Women - Socorro Rejany Sales Silva Trento; Alberto Madeiro; Andréa Cronemberger Rufino (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective To assess the sexual function and associated factors in postmenopausal women. Methods This a descriptive, cross-sectional study with 380 women aged 40 to 65 years, users of public health services in 2019. Questionnaires were applied on demographic characteristics, on climacteric symptoms (menopause rating scale) and on sexual function (sexual quotient, female version). Bivariate andmultiple analyses by logistic regression were performed, with adjusted odds ratios (ORad) and 95% confidence intervals (95%CIs). Results More than half (243/64%) of the participating women were at risk of sexual dysfunction, with lower scores in the domains of sexual desire and interest, comfort, orgasm, and satisfaction. Women with a partner (ORad 2.07; 95%CI 1.03-4.17) and those who reported sleep problems (ORad 2.72; 95%CI 1.77-4.19), depressed mood (ORad 2.03; 95%CI 1.32-3.10), sexual complaints (ORad 8.16; 95%CI 5.06-13.15), and vaginal dryness (ORad 3.44; 95%CI 2.22-5.32) showed greater chance of sexual dysfunction. Conclusion There was a high prevalence of sexual dysfunction, with the influence of conjugality and climacteric symptoms on sexual function.